Precursors of quasi-decadal dry-spells in the Central America Dry Corridor - Hidalgo León, Hugo G. (2019)
Although the hydric stress in Central America is generally low, there is a region relatively drier and prone to drought known as the Central America Dry Corridor (CADC). The area of interest is located mainly in the Pacific slope of Central America, from Chiapas in southern Mexico, to the Nicoya Peninsula in the Costa Rican North Pacific. Most of the region has experienced significant warming trends (1970–1999). On the contrary precipitation and the Palmer Drought Severity Index (PDSI) have mainly displayed non-significant trends. Analysis using the Standardized Precipitation Index and PDSI in the CADC, suggests a significant periodicity of severe and sustained droughts of around 10 years. The drought response has been associated with tropical heating that drives an atmospheric response through strengthening of the Hadley cell, which in turn produces higher pressure in the subtropical highs, and intensification of the trade winds (indexed by the Caribbean Low Level Jet). It is important to determine the commonness of severe and sustained droughts in the CADC to improve water resources planning, as this is a region that depends on subsistence agriculture and presents high social and economic vulnerabilities.